Philosophical Approaches in Islamic Studies - Ahmad Noviansah; Mizaniya Mizaniya (Journal of Indonesian Islamic Studies, 2024)
Philosophy and Religion, two different things but not necessarily contradictory. One of these efforts is to study Islam with a philosophical approach. Islam is required to be able to contribute to solving problems. Understanding Islam through a philosophical approach is intended to give meaning to something encountered, capture the wisdom, essence or essence contained in Islamic teachings so that in doing acts of worship do not feel empty, spiritual dryness and boredom in carrying out this approach views religious problems from a philosophical perspective and tries to offer solutions and solutions to problems with a critical-analytical method. The philosophical approach in the study of religion seeks to find explanations of the concepts of religious teachings by examining and finding a system of reason that humans can understand.